(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
This research shows the importance of tax incentives in reducing or limiting the environmental environment and its effects on the tax proceeds, as the researcher highlights the importance of using tax incentives. environment resulting from industrial activities. Where the researcher touched on the theoretical side of the research to the research problem represented by whether tax incentives can be used to reduce and limit environmental pollutants and the extent of this in the tax proceeds, The research hypothesis was formulated whether tax incentives can be used as an effective tool in reducing and limiting environmental pollutants and the extent of their impact on tax proceeds. Is there a significant relationship between tax incentives and environmental pollutants? Is there a significant relationship between tax incentives and tax proceeds? The researcher addressed In the theoretical aspect of the research, it refers to tax incentives and their importance, and then a review of the environment and its pollutants, and a study of tax accounting for brick factories by the General Authority for Taxes. Collecting information, where 120 questionnaires were distributed to the research sample(Companies Department and Business Department in the General Tax Authority) Statistical indicators were extracted by using the SPSS program for statistical analysis and using the questionnaire form using the five-point Likert scale for measurement and analysis. The researcher reached a set of conclusions, the most important of which is that tax incentives are an effective tool for developing and supporting For aspects of economic activity if new laws and instructions are enacted that are commensurate with granting the purpose for which they were found, especially in the field of reducing environmental pollutants.